A Brief Survey of the Theory of Auction. (December 2013) - Chatterjee, Rittwik
This is a brief survey of the theory of auction. We first discuss the types of agents who participate in an auction and their respective objectives. In the next section we briefly explain the concepts of standard auction, revenue equivalence theorem (perhaps the most cited result in auction theory, along with the result of Myerson on optimal auction), optimal auction, interdependent valuations, risk and some other commonly used concepts. Finally we discuss the theory of contest, as contests are essentially auctions where a part of the payment function is exogenously given to the contestants. JEL Classification: D44 (Auctions)